Influence of School Environment on Mental Health of Students at Formal Operational Stage of Cognitive Development - Malhotra, Taruna (INDIAN EDUCATIONAL REVIEW, 2015)
School is the miniature form of society. It is the place where a child spends half of the day and influence of school environment on personality, character and general well-being of student can’t be evaded. The functioning and management style of school affect the overall development of the child, especially at the formal operational stage of the cognitive development. To understand the importance of school environment it becomes crucial to decipher the influence of school environment on the mental health of students at formal operational stage. The purpose of the present investigation was to study the influence of different dimensions of school environment on the mental health of students across gender. The sample comprised 200 students of formal operational stage selected from the district of Rohtak in the state of Haryana. School Education Inventory by Mishra (1989) and Mental Health Battery (MHB-ss) by Singh & Gupta (2000) were administered to ascertain the influence of school environment and mental health of students of formal operational stage. Descriptive statistics was used to analyse the data. The analysis revealed that creative stimulation (CRS), acceptance (ACC) and control (CON) positively influence the mental health whereas permissiveness (PER) affects the mental health of students of formal operational stage in negative direction.